Culture-bearing Women. The Black Women Renaissance and Cultural Nationalism - Penier, Izabella (De Gruyter, 2019)
This study examines the Black Women's Renaissance (BWR) - the flowering of literary talent among African American women at the end of the 20th century. It focuses on the historical and heritage novels of the 1980s and the vexed relationship between black cultural nationalism and black feminism. It argues that when the nation seemingly fell out of fashion, black women writers sought to re-create what Renan called "a soul, a spiritual principle" for their ethnic group. BWR narratives, especially those associated with womanism, appreciated "culture bearing" mothers as cultural reproducers of the nation and transmitters of its values. In this way, the writers of the BWR gave rise to "matrifocal" cultural nationalism that superseded masculine cultural nationalism of the previous decade and made black women, instead of black men, principal agents/carriers of national identity. This monograph argues that even though matrifocal nationalism empowered women, ultimately it was a flawed project. It promoted gender and cultural essentialism, i.e. it glorified black motherhood and mother-daughter bonding and condemned other, more radical models of black female subjectivity. Moreover, the BWR, vivified by middle-class and educated black women, turned readers' attention from more contentious social issues, such as class mobility or wealth redistribution. The monograph compares the cultural nationalist novels of the 1980s with social protest novels written by the same authors in the 1970s and explains the rationale behind the change in their aesthetic and political agenda. It also contrasts novels written by womanist writers (Toni Morrison, Alice Walker, Gloria Naylor to name just a few) and by African Caribbean immigrant or second-generation writers (Audre Lorde, Paule Marshall, Jamaica Kincaid and Michelle Cliff) to show that, on the score of cultural nationalism, the BWR was not a monolithic phenomenon. African American and African Caribbean women writers collectively contribu